Seminar on Film Industries in Asia and Europe a platform of experiences' sharing - Feilberg, Lars (Singapore Asia-Europe Foundation (ASEF), 2005)
This publication contains basic information on existing models of support and regulation in various countries that address key issues in the objectives to create and maintain national film industry to the benefit of cultural diversity, art and entertainment. There is no single factor to the success of national film industry, and the following are all issues to be addressed: education of professionals, talent development, project development, means of production, and means of financing, subsidies, promotion, distribution, exhibition, regulations, network, organisation and a place to discuss and implement a national film policy.
"2-3 June 2005, Kuala Lumpur, Malaysia"
"Seminar on Film Industries' Models in Asia and Europe : a platform for experiences' sharing"--T. p. verso.
Includes biographies of speakers and glossary (pages 155-157).
A gift of Dr. Victor T. Valbuena.
Keywords: Motion picture industry -- Asia -- Congresses; Motion picture industry -- Europe -- Congresses